Exertional Leg Pain in Patients With and Without Peripheral Arterial Disease - Wang, Jimmy C. (Circulation, 2005)
BACKGROUND: Although exertional leg pain is a hallmark of peripheral arterial disease (PAD) and can occur in persons without PAD, symptom variation has received inadequate attention. METHODS AND RESULTS: Three cohort studies were combined for cross-sectional analysis. The San Diego Claudication Questionnaire assessed exertional leg pain. PAD was defined as ankle brachial index (ABI) ≤0.90 or history of lower-extremity revascularization. Of 3658 subjects, 3629 were analyzed after exclusions. Of these, 24.1% had PAD in 1 or both legs. There was a stepwise decrease in average ABI, from no pain to pain on exertion and rest, noncalf pain, atypical calf pain, and classic claudication (P=0.002). When stratified by PAD, this trend was no longer significant. Legs with ABIs >0.90 and revascularization had pain distributions intermediate between that of normal legs (ABI, 1.00 to 1.39) and legs with ABIs ≤0.90. Compared with normal legs, legs with low-normal (0.91 to 0.99) and high-normal (≥1.40) ABIs had higher pain rates, suggesting borderline disease and vascular stiffness, respectively. Multivariable logistic regression models showed that ABI was a strong correlate of pain category throughout the ABI range. Independently of ABI, age, male sex, diabetes, smoking history, high body mass index, myocardial infarction, and previous revascularization were all significant correlates of exertional leg pain. CONCLUSIONS: No category of exertional leg pain was sufficiently sensitive or specific for routine PAD diagnosis. Legs with low-normal and high-normal ABIs appeared to have ischemic leg pain; thus, a “normal ABI” is likely to range from 1.00 to 1.39. In addition to ABI, several risk variables were independent correlates of exertional leg pain.